Analisis Pentingnya Parafrase pada Penulisan Artikel Ilmiah Sebagai Upaya Menghindari Plagiarisme - Lubis, Fitriani; Silaban, Andreas Fernandes; Siregar, Anna Sari Asbabul Jannah; Girsang, Aulia Angraini; Situmorang, Desi Natalye Br.; Purba, Grace Silvia Anastasia; Siregar, Novita Angelin; Devi, Tiara Andra (Jurnal Pendidikan Non formal, 2023)
Paraphrasing is the process of conveying an idea by elaborating on different words while maintaining the meaning or message of the original source. It is crucial to retain key information and main ideas from the original source, but the use of sentence structure, grammar, and word choice must be altered in such a way that it still adheres to the formal academic language standards of scholarly articles. This study aims to explore the role of paraphrasing in preventing plagiarism. The research employs a qualitative method with a literature review approach, utilizing data obtained from accredited scholarly articles. The findings indicate that paraphrasing plays a significant role in avoiding plagiarism and facilitates readers in comprehending the conveyed ideas. Consequently, it can be concluded that paraphrasing enhances the originality, maintains coherence, and ensures clarity in scholarly articles.